2021
DOI: 10.1007/s11695-021-05735-w
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Results of Laparoscopic Sleeve Gastrectomy: Retrospective Matched Comparison with Laparoscopic Adjustable Gastric Banding—Is There a Significant Difference in Long Term?

Abstract: Background The laparoscopic sleeve gastrectomy (LSG) is the most common bariatric procedure performed worldwide while the laparoscopic adjustable gastric banding (LAGB) has been almost abandoned. Aim of this study was to retrospectively assess 10-year outcomes of LSG through a matched comparison with LAGB. Materials and Methods Retrospective search of prospectively maintained database of our university was carried out to find all patients that underwent LS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Hauters et al [ 18 ] reported that 41% of patients reached this goal at 10 years after SG. This was further supported by an additional retrospective study reporting 48.6% of patients reaching EWL > 50 [ 19 ]. We agree with conclusions drawn in these studies that SG may be of benefit for selected patients.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Hauters et al [ 18 ] reported that 41% of patients reached this goal at 10 years after SG. This was further supported by an additional retrospective study reporting 48.6% of patients reaching EWL > 50 [ 19 ]. We agree with conclusions drawn in these studies that SG may be of benefit for selected patients.…”
Section: Discussionmentioning
confidence: 54%
“…Similarly, Chang et al [ 21 ] reported 39.6% remission of T2D, 78.4% for HTN, and 51.3% for dyslipidemia. On the contrary, Musella et al [ 19 ] showed in their cohort showed 0% remission of T2D and 51.4% remission of HTN. Our results showed 47% remission for T2D, 43.7% remission for HTN, and 48.4% remission for hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Revisions to non-anastomotic operations (i.e., gastric band to sleeve gastrectomy) were not compared, as we restricted our analysis to more complex revisions (revisions to an anastomotic case). In that regard, as the population of sleeve gastrectomy patients continues to increase, we believe revisions to anastomotic cases are likely to increase due to issues related to weight regain and reflux [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical technique has been described in detail elsewhere [7], but a brief description is reported below for completeness of the article. For LSG, a five-trocar approach (3 × 12 mm, 2 × 5 mm) was used.…”
Section: Surgical Techniquementioning
confidence: 99%